2008
DOI: 10.1080/01612840701869239
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms of Hepatitis C

Abstract: More than 4 million (2%) people in the United States have been infected with the hepatitis C virus, of whom 2.7 million are chronically infected. The current treatment for chronic hepatitis C patients is Interferon and ribavirin combination therapy, which is associated with numerous neuropsychiatric side effects. The most common are fatigue, depression, cognitive dysfunction, and anxiety. Early identification and treatment of these symptoms may not only improve the patient's mental health, but also may increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, it remains unclear why up to 50% of patients with noncirrhotic CLD have these disorders long before the occurrence of cirrhosis 25 . Although this psychiatric comorbidity is common in all CLD, most of the published studies are based on an estimate of depression and anxiety in liver transplant candidate or patients after liver transplatation 7,29,14,15,27 , and patients with chronic viral hepatitis [28][29][30] . As reported in the literature, there is no difference in the level of depression and anxiety among candidates for liver transplantation and patients with liver disease who are not on the list for transplantation 24 , and therefore we estimate that the scores for depression and anxiety between these two groups of patients are comparable 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear why up to 50% of patients with noncirrhotic CLD have these disorders long before the occurrence of cirrhosis 25 . Although this psychiatric comorbidity is common in all CLD, most of the published studies are based on an estimate of depression and anxiety in liver transplant candidate or patients after liver transplatation 7,29,14,15,27 , and patients with chronic viral hepatitis [28][29][30] . As reported in the literature, there is no difference in the level of depression and anxiety among candidates for liver transplantation and patients with liver disease who are not on the list for transplantation 24 , and therefore we estimate that the scores for depression and anxiety between these two groups of patients are comparable 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because only a small number of studies have found no significant differences between depressed patients and health controls in short-term and working memory [Purcell et al, 1997[Purcell et al, , 1998] and attention [Albus et al, 1996;Sweeney et al, 2000]. In addition, psychiatric morbidity is known to be higher among patients infected with HCV when compared to the general population [Yovtcheva et al, 2001;el-Serag et al, 2002;Batista-Neves et al, 2008;Saunders, 2008] and the presence of mental disorders at the time of neuropsychological evaluation may be a factor contributing to the poorer cognitive performance found in this population [Weissenborn et al, 2004;Perry et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Though initially attributed to hepatic encephalopathy, cognitive dysfunction has also been noted prior to onset of liver dysfunction (Forton et al, 2002) . The HCV-associated cognitive dysfunction has been attributed to psychiatric morbidity or intravenous substance abuse that are more prevalent among patients infected with HCV compared with population rates (Batista-Neves et al, 2009; El-Serag, Kunik M, Richardson P, & Rabeneck, 2002; Perry et al, 2008; Saunders, 2008). Others have pointed to antiviral drugs used to treat HCV infections as those drugs can increase rates of depression and associated cognitive dysfunction (Reichenberg, Gorman, & Dieterich, 2005) .…”
Section: Introductionmentioning
confidence: 99%